User interface design practice for the web in New Zealand. (16th July 2008) - Lal, Ramesh; Overmyer, Scott P.
In a survey of 62 enterprises in New Zealand, including the six major universities, we were interested in finding out the state of industrial and educational practice with respect to the field of user interface design for the web. Our research revealed that usability issues seem to have taken a backseat to other kinds of development concerns. There is general lack of formal education, knowledge and skills in usability methods, processes and techniques amongst designers and developers. We also found that most universities in New Zealand offer one or two Human-Computer Interaction (HCI) courses within their information technology undergraduate degree programmes as electives. Conversely, our research shows that elsewhere internationally, HCI has become a major area of study especially where usability is a major industrial concern. We discuss the problem, its implications and possible remedies.